DIRECTIONS FOR THE DEVELOPMENT OF A MODERN SYSTEM OF STRATEGIC MANAGEMENT IN UNIVERSITIES - Ochilova Gulnoza Odilovna; Kadyrov Abdulaziz Rahmandzhanovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
The prepared article examines the theoretical foundations of the formation of a management system in higher educational institutions, which are considered pressing problems today. In addition, the author’s approach to management concepts and the organizational and economic mechanism of management systems, based on the results of an analysis of the problems observed in the field, features that must be taken into account in the process of improving the management system. higher education institution management system, main trends and tendencies.